2019
DOI: 10.3390/w11102029
|View full text |Cite
|
Sign up to set email alerts
|

Improving Parameter Transferability of GR4J Model under Changing Environments Considering Nonstationarity

Abstract: Hydrological nonstationarity has brought great challenges to the reliable application of conceptual hydrological models with time-invariant parameters. To cope with this, approaches have been proposed to consider time-varying model parameters, which can evolve in accordance with climate and watershed conditions. However, the temporal transferability of the time-varying parameter was rarely investigated. This paper aims to investigate the predictive ability and robustness of a hydrological model with time-varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…This model is based on the cascade of the reservoirs and links rainfall to runoff (Anshuman et al, 2021;Zhang et al, 2021;Chiew et al, 2022). Scientifically, the model was improved by Perrin et al (2003) and applied by many scholars such as (Ruelland et al, 2010;Kunnath-Poovakka and Eldho, 2019;Zeng et al, 2019;Kodja et al, 2020;Zafari et al, 2022) in various climate regions. The GR4J is a global conceptual model for rainfall-runoff that needs 4 parameters: X 1 , the maximum volume of the production stock (mm); X 2 , the coefficient of groundwater exchange (mm); X 3 , the maximum volume of the routing store (mm); and X 4 , the time highest ordinate of hydrograph unit UH1 (day) (Figure 2).…”
Section: Hydrological Modelmentioning
confidence: 99%
“…This model is based on the cascade of the reservoirs and links rainfall to runoff (Anshuman et al, 2021;Zhang et al, 2021;Chiew et al, 2022). Scientifically, the model was improved by Perrin et al (2003) and applied by many scholars such as (Ruelland et al, 2010;Kunnath-Poovakka and Eldho, 2019;Zeng et al, 2019;Kodja et al, 2020;Zafari et al, 2022) in various climate regions. The GR4J is a global conceptual model for rainfall-runoff that needs 4 parameters: X 1 , the maximum volume of the production stock (mm); X 2 , the coefficient of groundwater exchange (mm); X 3 , the maximum volume of the routing store (mm); and X 4 , the time highest ordinate of hydrograph unit UH1 (day) (Figure 2).…”
Section: Hydrological Modelmentioning
confidence: 99%
“…Hydrological nonstationary has brought great challenges to the reliable applications of hydrological models with time-invariant parameters. Two papers [7,8] investigate the predictive ability and robustness of a hydrological model under changing environments. In [7], the authors propose a new method based on empirical mode decomposition (EMD) to synthesize and generate data which be interfered with the non-stationary problems.…”
Section: Summary Of the Papers In The Special Issuementioning
confidence: 99%
“…The new synthetic and historical flow data were used to simulate the water supply system of the Hushan reservoir in Taiwan, and the compared results show that the synthetic data are like the historical flow distribution. In [8], the authors investigate the predictive ability and robustness of a conceptual hydrological model (GR4J) with time-varying parameter under changing environments. The results show that the performance of streamflow simulation was improved when applying the time-varying parameters.…”
Section: Summary Of the Papers In The Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The GR4J model, as a lumped conceptual model, has been widely applied in various climate regions of the world because of its distinctive characteristics in principle and structure (Boumenni et al, 2017;Sezen and Partal, 2019). Zeng et al (2019) investigated the predictive ability and robustness of the GR4J model with timevarying parameters under changing environments and improved the performance of streamflow simulations in Wei River Basin. Ghimire et al (2020) used a range of hydrological modelling approaches for flow simulation and forecasting in the Ayeyarwady Basin and revealed that the GR4J model performed best in simulations and yielded the least biases in daily flow forecasting.…”
Section: Introductionmentioning
confidence: 99%